Analisis dan Pemeringkatan Faktor Kritis yang Mempengaruhi Mutu Pengelasan Struktur Baja Menggunakan Relative Importance Index (RII) - Muhammad Firdaus; Mardiaman Mardiaman (Universitas Batanghari Jambi, 2026)
Welding quality plays a crucial role in determining the strength, safety, and long-term performance of structural steel construction. Welding defects may lead to rework, project delays, additional costs, and reduced structural reliability. Therefore, identifying and prioritizing the factors influencing welding quality is essential for improving construction performance and quality management practices. This study aims to identify and rank the critical factors affecting structural steel welding quality using the Relative Importance Index (RII) method. A quantitative survey approach was employed in this study. Data were collected from 100 construction professionals, including engineers, welders, quality control personnel, welding inspectors, supervisors, and project practitioners involved in structural steel works. The questionnaire was developed based on the AWS D1.1 standard and relevant literature and distributed through Google Forms via WhatsApp between March and April 2026. The research instrument consisted of 24 causal-factor indicators grouped into six dimensions, namely technical aspects, documentation, human resources, supervision, management, and work environment, as well as five welding-quality outcome indicators. Reliability testing showed that the overall instrument achieved a Cronbach’s Alpha value of 0.984, indicating excellent internal consistency. The results of the Relative Importance Index analysis revealed that the five most influential factors affecting welding quality were quality control supervision before, during, and after welding activities, cleanliness of the welding area from contaminants, compliance with AWS D1.1 standards, availability of competent welding inspectors, and the use of calibrated and well-maintained welding equipment. These findings indicate that welding quality is influenced not only by technical factors but also by effective supervision systems, personnel competency, and adherence to quality management procedures. The study provides practical guidance for contractors, consultants, owners, and quality management teams in prioritizing quality improvement strategies for structural steel welding projects.